Carbon negative electrode material precursor and preparation method and application thereof, carbon negative electrode material and preparation method and application thereof, and lithium ion battery

By using a mixture of specific petroleum coke as the precursor of carbon anode material and carrying out coating and graphitization, the problem of insufficient specific capacity and rate performance of existing carbon anode materials is solved, and the improvement of material performance and the reduction of production costs are achieved.

CN119822364APending Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311320567.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The specific capacity and rate performance of existing carbon anode materials need to be further improved.

Method used

Petroleum coke with specific microscopic and macroscopic characteristics is used as the precursor of the carbon anode material. By mixing the first petroleum coke, the second petroleum coke and the third petroleum coke, and carrying out coating and graphitization, a carbon anode material with high specific capacity and rate performance is prepared.

Benefits of technology

It has achieved the improvement of the specific capacity and rate performance of carbon anode materials, expanded the range of raw materials selection, reduced production costs, and has high application potential in the field of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004490851580000121
    Figure BDA0004490851580000121
  • Figure BDA0004490851580000131
    Figure BDA0004490851580000131
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a carbon negative electrode material precursor and a preparation method and application thereof, a carbon negative electrode material and a preparation method and application thereof, and a lithium ion battery. The carbon negative electrode material precursor comprises first petroleum coke (a1, k1), second petroleum coke (a2, k2) and third petroleum coke (a3, k3), and a1, a2 and a3 respectively represent the total content of large sheets and fiber structures in anisotropic structures of scorched particles; k1, k2 and k3 respectively represent the length-width ratio of the scorched particles; the first petroleum coke meets the following conditions: 75% < = a1 < 90%, and 1.7 < = k1 < 1.9; the second petroleum coke satisfies the following conditions: 65% < = a2 < 80%, and 1.5 < = k2 < 1.7; and the third petroleum coke satisfies the following conditions: 40% < = a3 < 60%, and 1 < = k3 < 1.3. By adopting the carbon negative electrode material precursor disclosed by the invention, the subsequently prepared carbon negative electrode material has relatively high specific capacity and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon negative electrode material precursor and a preparation method and application thereof, a carbon negative electrode material and a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] At present, with the rapid development of electric vehicles and portable devices, the demand for high-performance secondary batteries continues to grow. Lithium-ion batteries have the characteristics of high energy density, high cycle stability and environmental friendliness, which have attracted widespread attention from researchers. Effective ways to improve the energy storage capacity of lithium-ion batteries include improving the electrochemical properties of materials and structural design. As an important component of lithium-ion batteries, negative electrode materials often need to be modified to improve electrochemical activity. Petroleum coke is a high-quality artificial graphite raw material with advantages such as high conductivity, easy graphitization, low ash content and low metal content. In order to further improve the electrochemical properties of artificial graphite, improvements can be made in the preparation of raw materials and production processes of high-quality coke (ZL202010646862.7). In addition, there have been many related studies on structural design and modification, such as particle size adjustment, surface carbon coating, etc. (ZL202010207606.8, ZL201711351496.7, ZL201710616466.8, ZL202011552394.3). However, materials with high graphitization degree have small interlayer spacing, regular lamellar structure, and high degree of anisotropy. Due to the existence of lithium ion intercalation storage dynamics and volume expansion effects, there is still room for improvement in specific capacity and rate performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the problem that the specific capacity and rate performance of existing carbon negative electrode materials need to be further improved, and to provide a carbon negative electrode material precursor and a preparation method and application thereof, a carbon negative electrode material and a preparation method and application thereof, and a lithium ion battery. The use of the carbon negative electrode material precursor of the present invention can make the subsequently prepared carbon negative electrode material have a higher specific capacity and rate performance.

[0004] In order to achieve the above-mentioned object, the present invention provides a carbon negative electrode material precursor on one hand, wherein the carbon negative electrode material precursor comprises: a first petroleum coke (a1, k1), a second petroleum coke (a2, k2) and a third petroleum coke (a3, k3), wherein a1, a2 and a3 respectively represent the total content of large pieces and fiber structures in the anisotropic structure of the coke particles; k1, k2 and k3 respectively represent the aspect ratio of the coke particles;

[0005] Among them, the first petroleum coke satisfies: 75%≤a1<90%, and 1.7≤k1<1.9; the second petroleum coke satisfies: 65%≤a2<80%, and 1.5≤k2<1.7; the third petroleum coke satisfies: 40%≤a3<60%, and 1≤k3<1.3.

[0006] Preferably, based on the total weight of the first petroleum coke, the second petroleum coke and the third petroleum coke, the mass content of the first petroleum coke is 45-65%, preferably 50-60%; the mass content of the second petroleum coke is 15-35%, preferably 20-30%; the mass content of the third petroleum coke is 10-30%, preferably 15-25%.

[0007] The second aspect of the present invention provides a method for preparing a carbon negative electrode material precursor, the method comprising mixing the first petroleum coke (a1, k1) described in the first aspect, the second petroleum coke (a2, k2) and the third petroleum coke (a3, k3).

[0008] The third aspect of the present invention provides an application of the carbon negative electrode material precursor described in the first aspect in a carbon negative electrode material.

[0009] A fourth aspect of the present invention provides a method for preparing a carbon negative electrode material, the preparation method comprising the following steps:

[0010] (1) coating the carbon negative electrode material precursor and high-temperature asphalt described in the first aspect to obtain a coated product;

[0011] (2) The coated product is graphitized in a non-oxidizing atmosphere to obtain a carbon negative electrode material.

[0012] The fifth aspect of the present invention provides a carbon negative electrode material prepared by the preparation method described in the fourth aspect.

[0013] The sixth aspect of the present invention provides an application of the carbon negative electrode material described in the fifth aspect in a lithium ion battery.

[0014] A seventh aspect of the present invention provides a lithium ion battery, comprising: the carbon negative electrode material described in the fifth aspect.

[0015] Through the above technical solution, the beneficial effects of the present invention include:

[0016] The carbon negative electrode material precursor provided by the present invention is obtained by combining petroleum coke with specific microscopic characteristics and macroscopic characteristics, wherein the microscopic characteristics refer to the total content of large pieces and fiber structures in the anisotropic structure of the coke particles, and the macroscopic characteristics refer to the aspect ratio of the coke particles, so that the carbon negative electrode material has higher specific capacity and rate performance.

[0017] The carbon negative electrode material precursor provided by the present invention is used to prepare the carbon negative electrode material, which realizes the classified application of different petroleum cokes, expands the selection range of raw materials, improves the utilization rate of materials, reduces production costs, and has high application potential in the field of lithium ion batteries.

[0018] The method for preparing the carbon negative electrode material provided by the present invention simplifies the process flow and is convenient for industrial production. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] In the present invention, unless otherwise specified, "first", "second" and "third" do not indicate a sequence or limit the materials or steps, but are only used to distinguish or indicate that they are not the same material or step. For example, "first", "second" and "third" in "first petroleum coke", "second petroleum coke" and "third petroleum coke" are only used to indicate that they are not the same petroleum coke.

[0021] On one hand, the present invention provides a carbon negative electrode material precursor, which comprises: a first petroleum coke (a1, k1), a second petroleum coke (a2, k2) and a third petroleum coke (a3, k3), wherein a1, a2 and a3 respectively represent the total content of large pieces and fiber structures in the anisotropic structure of the coke particles; k1, k2 and k3 respectively represent the aspect ratio of the coke particles;

[0022] Among them, the first petroleum coke satisfies: 75%≤a1<90%, and 1.7≤k1<1.9; the second petroleum coke satisfies: 65%≤a2<80%, and 1.5≤k2<1.7; the third petroleum coke satisfies: 40%≤a3<60%, and 1≤k3<1.3.

[0023] In the present invention, the units of a1, a2 and a3 are all percentages.

[0024] In the present invention, the definition of petroleum coke is well known to those skilled in the art and will not be described in detail herein.

[0025] In the present invention, unless otherwise specified, the first petroleum coke (a1, k1) refers to the first petroleum coke satisfying: the total content of large flakes and fiber structures in the anisotropic structure of the coke particles is a1, and the aspect ratio of the coke particles is k1; similarly, the second petroleum coke (a2, k2) refers to the second petroleum coke satisfying: the total content of large flakes and fiber structures in the anisotropic structure of the coke particles is a2, and the aspect ratio of the coke particles is k2; the third petroleum coke (a3, k3) refers to the third petroleum coke satisfying: the total content of large flakes and fiber structures in the anisotropic structure of the coke particles is a3, and the aspect ratio of the coke particles is k3.

[0026] In the present invention, unless otherwise specified, the total content of large flakes and fiber structures in the anisotropic structure of the coke particles refers to the total content of large flakes, short fibers, fine fibers and coarse fibers in the anisotropic structure of the coke particles. The above-mentioned large flakes, short fibers, fine fibers and coarse fibers have definitions well known to those skilled in the art, and the present invention will not be described in detail here.

[0027] In the present invention, the total content parameter of large pieces and fiber structures in the anisotropic structure of the coke particles and the aspect ratio parameter of the coke particles are characterized by taking pictures under a polarizing microscope, and the anisotropic structure of the coke particles is quantitatively analyzed using Image J analysis software, and the aspect ratio of the coke particles is measured. When analyzing the optical tissue structure, points are taken at a point spacing of 300 μm and a line spacing of 500 μm, and the type of anisotropic structure at each point is analyzed according to the dot counting method.

[0028] According to the present invention, preferably, based on the total weight of the first petroleum coke, the second petroleum coke and the third petroleum coke, the mass content of the first petroleum coke is 45-65%, preferably 50-60%, for example, it can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, and any value in the range formed by any two of these values; the mass content of the second petroleum coke is 15-35%, preferably 20-30%, for example, it can be 15%, 16%, 17%, 18%, 19 %, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, and any value in the range formed by any two of these values; the mass content of the third petroleum coke is 10-30%, preferably 15-25%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, and any value in the range formed by any two of these values. Adopting this preferred embodiment is conducive to further improving the specific capacity and rate performance of the carbon negative electrode material.

[0029] According to the present invention, preferably, the D50 of the first petroleum coke (a1, k1) is 15-20 μm, for example, it can be 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, and any value in the range formed by any two of these values.

[0030] According to the present invention, preferably, the D50 of the second petroleum coke (a2, k2) is 10-15μm, and preferably not 15μm, for example, it can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, and any value in the range formed by any two of these values.

[0031] According to the present invention, preferably, the D50 of the third petroleum coke (a3, k3) is 1-5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, and any value in the range formed by any two of these values.

[0032] The present invention has no particular limitation on the method for obtaining the above-mentioned D50 petroleum coke, which can be obtained by conventional technical means in the art. The present invention uses the method of crushing and screening as an example.

[0033] The second aspect of the present invention provides a method for preparing a carbon negative electrode material precursor, the method comprising mixing the first petroleum coke (a1, k1) described in the first aspect, the second petroleum coke (a2, k2) and the third petroleum coke (a3, k3).

[0034] According to the present invention, preferably, the mixing process includes: S1, mixing the first petroleum coke (a1, k1) and the second petroleum coke (a2, k2) to obtain a first mixture; S2, mixing the first mixture and a third petroleum coke (a3, k3).

[0035] The inventors of the present invention found that large-sized and relatively large-sized petroleum cokes are first mixed to serve as a skeleton; and then mixed with small-sized petroleum coke to fill the gaps. The synergistic effect of the three different particle sizes of petroleum coke is conducive to the subsequent formation of a good coating effect, which in turn is conducive to improving the specific capacity and rate performance of the carbon negative electrode material.

[0036] According to the present invention, preferably, in S2, part of the third petroleum coke (a3, k3) is first mixed with the first mixed material, and then the remaining part of the third petroleum coke is added for mixing, and the weight ratio of the part of the third petroleum coke to the remaining part of the third petroleum coke is 0.5-2: 1. With this preferred embodiment, adding small particles of the third petroleum coke in batches can make the mixing more uniform, fully fill the gaps, and form a better coating later.

[0037] According to a specific embodiment of the present invention, the mixing is carried out in a high-speed mixer.

[0038] The present invention has no particular limitation on the speed and mixing time of the high-speed mixer, which can be appropriately selected according to specific circumstances to achieve uniform mixing.

[0039] The third aspect of the present invention provides an application of the carbon negative electrode material precursor described in the first aspect in a carbon negative electrode material.

[0040] The carbon negative electrode material precursor provided by the present invention is used to prepare the carbon negative electrode material, which realizes the classified application of different petroleum cokes, expands the selection range of raw materials, improves the utilization rate of materials, reduces production costs, and has high application potential in the field of lithium ion batteries.

[0041] A fourth aspect of the present invention provides a method for preparing a carbon negative electrode material, the preparation method comprising the following steps:

[0042] (1) coating the carbon negative electrode material precursor and high-temperature asphalt described in the first aspect to obtain a coated product;

[0043] (2) The coated product is graphitized in a non-oxidizing atmosphere to obtain a carbon negative electrode material.

[0044] According to the present invention, preferably, in step (2), the weight ratio of the carbon negative electrode material precursor and the high-temperature asphalt is 80-95:5-20, for example, it can be 80:20, 85:15, 86:14, 87:13, 88:12, 89:11, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, and any value in the range composed of any two numerical values, preferably 85-90:10-15.

[0045] It should be noted that in the present invention, when the weight ratio of the carbon negative electrode material precursor and the high temperature asphalt is less than 80:20, the obtained negative electrode material semi-finished product will be in agglomerate or block shape; when the weight ratio of the carbon negative electrode material precursor and the high temperature asphalt is greater than 95:5, it cannot fully play the role of coating and filling the internal pores and cracks; there are still some exposed parts on the surface of the negative electrode material, which will react with the solvent in the electrolyte and affect the charge and discharge efficiency. Therefore, whether the weight ratio of the carbon negative electrode material precursor and the high temperature asphalt is less than 80:20 or greater than 95:5, it will affect the performance of the final product.

[0046] In the present invention, the high temperature asphalt has a definition well known to those skilled in the art.

[0047] According to the present invention, preferably, the softening point of the high temperature asphalt is 105-120°C.

[0048] The softening point parameter of the high temperature asphalt of the present invention is obtained by testing using a Mettler DP70 softening point tester.

[0049] According to the present invention, preferably, the quinoline insoluble content of the high-temperature asphalt is ≤0.2wt%.

[0050] The quinoline insoluble content parameter of the high-temperature asphalt described in the present invention is measured according to the GB / T 2293-2019 method.

[0051] The use of high-temperature asphalt with the above characteristics is conducive to forming a more complete and uniform coating.

[0052] It should be noted that when the content of quinoline insoluble matter is too high, small particles will be formed, which will affect the coating effect and reduce the graphitization degree of the coated product.

[0053] The present invention has a wide range of selections for the type of high-temperature asphalt, which can be a conventional choice in the field, as long as the above-mentioned characteristic parameters are met. The high-temperature asphalt can be high-temperature coal asphalt or high-temperature petroleum asphalt. In order to increase the gram capacity of the carbon negative electrode material and reduce pollution, preferably, the high-temperature asphalt is high-temperature petroleum asphalt.

[0054] According to the present invention, preferably, the coating treatment conditions in step (1) include: temperature of 180-260° C. and time of 1-4 h.

[0055] Further preferably, the coating process includes: a first coating stage, a second coating stage and a third coating stage; wherein,

[0056] The conditions of the first coating stage include: heating to 180-260°C, preferably 200-240°C, at a heating rate of 2-8°C / min; time of 1-4h, preferably 2-3h; rotation speed of 200-500rpm, preferably 300-400rpm;

[0057] The conditions of the second coating stage include: cooling at a cooling rate of 2-8°C / min to 10-15°C above the softening point of the high-temperature asphalt; the rotation speed is 100-300rpm, preferably 150-250rpm;

[0058] The third coating stage includes: cooling to 20-35°C at a cooling rate of 5-10°C / min.

[0059] The specific coating treatment mentioned above is beneficial to enhancing the bonding and coating effects.

[0060] According to the present invention, preferably, in step (2), the conditions of the graphitization treatment include: a temperature of 1000-3300° C. and a time of 20-48 h.

[0061] Further preferably, in step (3), the graphitization process includes: a first graphitization stage and a second graphitization stage; wherein:

[0062] The conditions of the first graphitization stage include: heating to 1000-1500°C, preferably 1100-1300°C, at a heating rate of 1-10°C / min; for 8-18h, preferably 10-15h;

[0063] The conditions of the second graphitization stage include: heating to 2500-3300° C., preferably 2800-3200° C., at a heating rate of 1-10° C. / min; and time of 15-30 h, preferably 20-25 h.

[0064] The above-mentioned specific graphitization treatment can obtain a carbon negative electrode material with a high degree of graphitization.

[0065] In the present invention, the non-oxidizing atmosphere has a wide selection range. Preferably, the non-oxidizing atmosphere includes but is not limited to nitrogen, argon, and helium, preferably nitrogen and argon.

[0066] Preferably, the method further comprises: screening the product of the graphitization treatment to obtain the carbon negative electrode material. In the present invention, the screening includes but is not limited to air flow ultrasonic screening and the like.

[0067] The fifth aspect of the present invention provides a carbon negative electrode material prepared by the preparation method described in the fourth aspect.

[0068] The sixth aspect of the present invention provides an application of the carbon negative electrode material described in the fifth aspect in a lithium ion battery.

[0069] A seventh aspect of the present invention provides a lithium ion battery, comprising: the carbon negative electrode material described in the fifth aspect.

[0070] The present invention will be described in detail below through examples.

[0071] Example 1

[0072] (1) In a high-speed mixer, at a speed of 1000 rpm, a first petroleum coke (87%, 1.84) with a D50 of 15 μm after crushing and screening and a second petroleum coke (72%, 1.61) with a D50 of 10 μm after crushing and screening were mixed for 1 hour to obtain a first mixture; 1 / 2 (by mass) of a third petroleum coke (51%, 1.23) with a D50 of 2 μm after crushing and screening was added to the first mixture and mixed for 0.5 hour, and then the remaining part of the third petroleum coke was added and mixed for 0.5 hour to obtain a carbon negative electrode material precursor; wherein the weight ratio of the first petroleum coke, the second petroleum coke and the third petroleum coke was 60:20:20;

[0073] (2) coating the above-mentioned carbon negative electrode material precursor and high-temperature petroleum asphalt (softening point of 106° C., quinoline insoluble content of 0.08 wt %) to obtain a coated product; wherein the weight ratio of the above-mentioned carbon negative electrode material precursor to the high-temperature asphalt is 88:12;

[0074] The conditions of the first coating stage include: heating to 220°C at a heating rate of 5°C / min for 2 hours and a rotation speed of 300 rpm; the conditions of the second coating stage include: cooling to 120°C at a cooling rate of 2°C / min and a rotation speed of 150 rpm; the third coating stage includes: cooling to 25°C at a cooling rate of 10°C / min;

[0075] (3) The coated product is graphitized in an argon atmosphere, wherein the conditions of the first graphitization stage include: heating to 1300°C at a heating rate of 5°C / min for 12 h; the conditions of the second graphitization stage include: heating to 3000°C at a heating rate of 5°C / min for 24 h. The obtained graphitized product is subjected to airflow ultrasonic screening to obtain the carbon negative electrode material S1.

[0076] Example 2

[0077] (1) In a high-speed mixer, at a speed of 1000 rpm, a first petroleum coke (77%, 1.72) with a D50 of 17 μm after crushing and screening and a second petroleum coke (68%, 1.57) with a D50 of 13 μm after crushing and screening were mixed for 1 hour to obtain a first mixture; 1 / 2 (by mass) of a third petroleum coke (58%, 1.28) with a D50 of 3 μm after crushing and screening was added to the first mixture and mixed for 0.5 hour, and then the remaining part of the third petroleum coke was added and mixed for 0.5 hour to obtain a carbon negative electrode material precursor; wherein the weight ratio of the first petroleum coke, the second petroleum coke and the third petroleum coke was 55:30:15;

[0078] (2) coating the above-mentioned carbon negative electrode material precursor and high-temperature petroleum asphalt (softening point of 106° C., quinoline insoluble content of 0.08 wt %) to obtain a coated product; wherein the weight ratio of the above-mentioned carbon negative electrode material precursor to the high-temperature asphalt is 90:10;

[0079] The conditions of the first coating stage include: heating to 200°C at a heating rate of 3°C / min for 3 hours and a rotation speed of 300 rpm; the conditions of the second coating stage include: cooling to 120°C at a cooling rate of 6°C / min and a rotation speed of 150 rpm; the third coating stage includes: cooling to 25°C at a cooling rate of 8°C / min;

[0080] (3) The coated product is graphitized in an argon atmosphere, wherein the conditions of the first graphitization stage include: heating to 1200°C at a heating rate of 3°C / min for 15 h; the conditions of the second graphitization stage include: heating to 3000°C at a heating rate of 6°C / min for 20 h. The obtained graphitized product is subjected to airflow ultrasonic screening to obtain a carbon negative electrode material S2.

[0081] Example 3

[0082] (1) In a high-speed mixer, at a speed of 1000 rpm, a first petroleum coke (82%, 1.79) with a D50 of 19 μm after crushing and screening and a second petroleum coke (79%, 1.67) with a D50 of 15 μm after crushing and screening were mixed for 1 hour to obtain a first mixture; 1 / 2 (by mass) of a third petroleum coke (44%, 1.1) with a D50 of 5 μm after crushing and screening was added to the first mixture and mixed for 0.5 hour, and then the remaining part of the third petroleum coke was added and mixed for 0.5 hour to obtain a carbon negative electrode material precursor; wherein the weight ratio of the first petroleum coke, the second petroleum coke and the third petroleum coke was 50:25:25;

[0083] (2) coating the above-mentioned carbon negative electrode material precursor and high-temperature petroleum asphalt (softening point of 106° C., quinoline insoluble content of 0.08 wt %) to obtain a coated product; wherein the weight ratio of the above-mentioned carbon negative electrode material precursor to the high-temperature asphalt is 88:12;

[0084] The conditions of the first coating stage include: heating to 220°C at a heating rate of 5°C / min for 2 hours and a rotation speed of 300 rpm; the conditions of the second coating stage include: cooling to 118°C at a cooling rate of 8°C / min and a rotation speed of 150 rpm; the third coating stage includes: cooling to 25°C at a cooling rate of 10°C / min;

[0085] (3) The coated product is graphitized in an argon atmosphere, wherein the conditions of the first graphitization stage include: heating to 1300°C at a heating rate of 4°C / min for 12 h; the conditions of the second graphitization stage include: heating to 3100°C at a heating rate of 5°C / min for 24 h. The obtained graphitized product is subjected to airflow ultrasonic screening to obtain the carbon negative electrode material S3.

[0086] Example 4

[0087] The method of Example 1 is followed, except that the D50 of the first petroleum coke is replaced by 15 μm, the D50 of the second petroleum coke is replaced by 17 μm, and the D50 of the third petroleum coke is replaced by 20 μm. Other conditions are the same, to obtain carbon negative electrode material S4.

[0088] Example 5

[0089] The method of Example 1 is followed, except that in step (2), the weight ratio of the carbon negative electrode material precursor and the high-temperature asphalt is replaced with 80:20 to obtain the carbon negative electrode material S5.

[0090] Example 6

[0091] The method of Example 1 is followed, except that the weight ratio of the first petroleum coke, the second petroleum coke and the third petroleum coke is 25:30:45, to obtain a carbon negative electrode material S6.

[0092] Example 7

[0093] The method of Example 1 is followed, except that the weight ratio of the first petroleum coke, the second petroleum coke and the third petroleum coke is 80:10:10, to obtain a carbon negative electrode material S7.

[0094] Test Example 1

[0095] The carbon negative electrode materials prepared in the examples are assembled specifically to obtain lithium-ion batteries.

[0096] Assemble the battery: The electrochemical performance of the half-cell was evaluated using a CR2032 button cell. The carbon negative electrode material, acetylene black and polyvinylidene fluoride prepared above were mixed in a mass ratio of 8:1:1 to obtain a slurry; the slurry was coated on a copper foil, dried at 90°C in a vacuum oven for 12 hours, and then pressed; 1 mol / L LiPF6 was dissolved in a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 as the electrolyte; metallic lithium was used as the counter electrode, and the half-cell was assembled in a glove box under an Ar atmosphere (H2O and O2 contents were both less than 0.01ppm).

[0097] Among them, using Xinwei BTS3000 battery tester, the above lithium-ion batteries were subjected to constant current charge and discharge tests between 0.01 and 3.0V, with a charge and discharge rate of 0.1C, and the first discharge specific capacity and first coulomb efficiency tests were performed. The test results are listed in Table 1.

[0098] Among them, the capacity of the above lithium-ion batteries was tested at 0.1C and 3C rates using a Xinwei BTS3000 battery tester to obtain rate performance. The test results are listed in Table 1.

[0099] Table 1

[0100]

[0101]

[0102] It can be seen from the results in Table 1 that the lithium ion battery assembled with the carbon negative electrode material prepared by the method of the present invention has a higher first discharge specific capacity and rate performance.

[0103] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A carbon negative electrode material precursor, characterized in that: The carbon negative electrode material precursor includes: a first petroleum coke (a1, k1), a second petroleum coke (a2, k2) and a third petroleum coke (a3, k3), wherein a1, a2 and a3 respectively represent the total content of large pieces and fiber structures in the anisotropic structure of the coke particles; k1, k2 and k3 respectively represent the aspect ratio of the coke particles; Among them, the first petroleum coke satisfies: 75%≤a1<90%, and 1.7≤k1<1.9; the second petroleum coke satisfies: 65%≤a2<80%, and 1.5≤k2<1.7; the third petroleum coke satisfies: 40%≤a3<60%, and 1≤k3<1.

3.

2. The carbon negative electrode material precursor according to claim 1, wherein: Based on the total weight of the first petroleum coke, the second petroleum coke and the third petroleum coke, the mass content of the first petroleum coke is 45-65%, preferably 50-60%; the mass content of the second petroleum coke is 15-35%, preferably 20-30%; the mass content of the third petroleum coke is 10-30%, preferably 15-25%; Preferably, the D50 of the first petroleum coke (a1, k1) is 15-20 μm; The D50 of the second petroleum coke (a2, k2) is 10-15 μm; The D50 of the third petroleum coke (a3, k3) is 1-5 μm.

3. A method for preparing a carbon negative electrode material precursor, the method comprising mixing the first petroleum coke (a1, k1) according to claim 1 or 2, the second petroleum coke (a2, k2) and the third petroleum coke (a3, k3); Preferably, the mixing process comprises: S1, mixing the first petroleum coke (a1, k1) and the second petroleum coke (a2, k2) to obtain a first mixed material; S2, mixing the first mixed material and the third petroleum coke (a3, k3); Preferably, in S2, part of the third petroleum coke (a3, k3) is first mixed with the first mixed material, and then the remaining part of the third petroleum coke is added and mixed, and the weight ratio of the part of the third petroleum coke to the remaining part of the third petroleum coke is 0.5-2:

1.

4. Use of the carbon negative electrode material precursor according to claim 1 or 2 in carbon negative electrode materials.

5. A method for preparing a carbon negative electrode material, characterized in that: The preparation method comprises the following steps: (1) coating the carbon negative electrode material precursor according to claim 1 or 2 and high-temperature asphalt to obtain a coated product; (2) The coated product is graphitized in a non-oxidizing atmosphere to obtain a carbon negative electrode material.

6. The preparation method according to claim 5, wherein: In step (1), the weight ratio of the carbon negative electrode material precursor to the high temperature asphalt is 80-95:5-20, preferably 85-90:10-15; Preferably, the softening point of the high temperature asphalt is 105-120°C; Preferably, the quinoline insoluble matter content of the high-temperature asphalt is ≤0.2wt%.

7. The preparation method according to claim 5, wherein: The coating treatment conditions in step (1) include: temperature of 180-260° C. and time of 1-4 h; Preferably, the coating process in step (1) includes: a first coating stage, a second coating stage and a third coating stage; wherein: The conditions of the first coating stage include: heating to 180-260°C at a heating rate of 2-8°C / min for 1-4h and a rotation speed of 200-500rpm; The conditions of the second coating stage include: cooling at a cooling rate of 2-8°C / min to 10-15°C above the softening point of the high-temperature asphalt, and a rotation speed of 100-300rpm; The third coating stage includes: cooling to 20-35°C at a cooling rate of 5-10°C / min.

8. The preparation method according to any one of claims 5 to 7, wherein: In step (2), the conditions of the graphitization treatment include: temperature of 1000-3300° C. and time of 20-48 h; Preferably, in step (2), the graphitization process includes: a first graphitization stage and a second graphitization stage; wherein: The conditions of the first graphitization stage include: heating to 1000-1500°C at a heating rate of 1-10°C / min for 8-18h; The conditions of the second graphitization stage include: heating to 2800-3300° C. at a heating rate of 1-10° C. / min for 15-30 hours.

9. A carbon negative electrode material obtained by the preparation method according to any one of claims 5 to 8.

10. Use of the carbon negative electrode material according to claim 9 in a lithium ion battery.

11. A lithium ion battery, characterized in that: The lithium-ion battery comprises: the carbon negative electrode material according to claim 9.

Citation Information

Patent Citations

  • A production method of a power type lithium ion battery anode material

    CN107293697A

  • Method for producing graphite negative-electrode material by using needle coke, and negative-electrode material

    CN108328613A

  • An efficient preparation method for high-capacity fast-charging graphite anode material

    CN111675212B

  • A method for preparing artificial graphite material for lithium-ion battery anode

    CN111825088B

  • Composite graphite anode materials, their preparation methods and applications, and lithium-ion batteries

    CN112661148B

Cited By

  • Lithium ion battery negative electrode material precursor, preparation method thereof and pre-carbonization furnace

    CN121020549A